A Study on RC Beams with Externally Bonded Carbon Fiber Reinforced Polymer (CFRP) Fabrics - R. Balamuralikrishnan; C. Antony Jeyasehar (Novel Perspectives of Engineering Research Vol. 10, 2022)
This paper explores the flexural behavior of carbon fiber reinforced polymer (CFRP) strengthened reinforced concrete (RC) beams. Strengthening with externally bonded CFRP fabric has shown to be applicable to many kinds of structures. Currently, this method has been applied to strengthen such structures as column, beams, walls, slabs, etc. A total of ten RC beams were cast and tested up to failure under monotonic and cyclic loads over an effective span of 3000 mm for flexural strengthening. Under-reinforced concrete beams were built for the beams. Under virgin conditions, eight beams were strengthened with bonded CFRP fabric in a single layer and two layers parallel to the beam axis at the bottom and tested to failure; the remaining two beams served as control specimens. All of the beams’ static and cyclic responses were assessed in terms of strength, stiffness, ductility ratio, and energy absorption capacity factor, compositeness between CFRP fabric and concrete, and failure mechanisms. The theoretical moment-curvature relationship and the load-displacement response of the strengthened beams and control beams were predicted by using FEA software ANSYS. Comparison has been made between the numerical (ANSYS) and the experimental results. The results show that the strengthened beams exhibit increased flexural strength, enhanced flexural stiffness, and composite action until failure. It is concluded that minimum two layers of CFRP fabric should be bonded to get the desired results. The strengthened beams RB1(single layer) and RB3 (two layer), exhibit 20 percent and 45% increase in flexural strength when compared to the control specimen and has close agreement with the experimental and numerical (ANSYS) results.